The multiplicity of halal standards: a case study of application to slaughterhouses - Abdallah, Ali; Abdelrahem, Mohammed; Pasqualone, Antonella (Journal of Ethnic Foods, 2021)
Food products suitable for Muslim consumers should be halal certified, particularly when their origins or production processes are doubtful. However, there is a multiplicity of halal standards. This situation may generate confusion, particularly for producers in Western countries who would like to certify their products in order to export them to Islamic countries. This study analyzed the reasons underlying the multiplicity of standards and reviewed the attempts of harmonization over time. Then, the case study of application to slaughterhouses was considered, by comparing four different halal standards (namely GSO 993:2015, OIC/SMIIC 1:2019, HAS 23103:2012, and MS 1500:2019) representative of different geographic areas. Animal stunning was critically examined, comparing tradition with modernity. The study evidenced that the basic requirements related to slaughtering are common to all the halal standards considered, but several differences occur in more specific details. Only a close collaboration between the authorities of all the countries involved in issuing halal certifications will lead to a homogeneous regulatory framework with unified certification and accreditation procedures, increasingly required in a globalized market.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Animal welfare; Food quality; Food standards; Geographic variability; Halal certification